2022
DOI: 10.3389/fchem.2022.944428
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofiber-based glucose sensors for glucose detection

Abstract: Diabetes is a chronic, systemic metabolic disease that leads to multiple complications, even death. Meanwhile, the number of people with diabetes worldwide is increasing year by year. Sensors play an important role in the development of biomedical devices. The development of efficient, stable, and inexpensive glucose sensors for the continuous monitoring of blood glucose levels has received widespread attention because they can provide reliable data for diabetes prevention and diagnosis. Electrospun nanofibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 287 publications
0
42
0
Order By: Relevance
“…It can be concluded that with the increase in the content of antibacterial active substances, the antibacterial activity of the fiber membrane packaging increased correspondingly, indicating that nanosilver and resveratrol had a synergistic effect on their antibacterial activity. Along this proof-of-concept demonstration and with the capability of electrospinning in creating complex nanostructures such as Janus particles, a tri-layer core-sheath and their combinations [ 95 , 96 , 97 ], many novel fiber membranes loaded with multiple active ingredients will be further developed for food packaging in the future, particularly from many bioactive molecules [ 98 , 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that with the increase in the content of antibacterial active substances, the antibacterial activity of the fiber membrane packaging increased correspondingly, indicating that nanosilver and resveratrol had a synergistic effect on their antibacterial activity. Along this proof-of-concept demonstration and with the capability of electrospinning in creating complex nanostructures such as Janus particles, a tri-layer core-sheath and their combinations [ 95 , 96 , 97 ], many novel fiber membranes loaded with multiple active ingredients will be further developed for food packaging in the future, particularly from many bioactive molecules [ 98 , 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…The basic principle of electrostatic spinning is the viscosity of the polymer solution through Coulomb force stretching, where spinning polymer droplets (due to Coulomb and gravity forces greater than the surface tension) gradually change from hemispherical to conical, and from a cone pointed outward to a liquid, and the solvents evaporate quickly, creating fine fibers in the receiving plate, as shown in Figure 2 , eventually forming nanometer fiber membranes [ 70 , 71 , 72 , 73 , 74 , 75 ]. NFs have excellent properties such as small diameter, large porosity, large specific surface area, and good mechanical energy along the fiber axis; the fiber morphology can be controlled by adjusting the parameter settings [ 76 , 77 ]. The influencing factors can be divided into three categories, including electrospinning parameters (voltage, needle diameter, feed rate, distance from needle to collector), solution properties (polymer molecular weight, concentration, solvent, viscosity, conductivity, surface tension), and environment parameters (temperature and relative humidity).…”
Section: Preparation Of Pvdf Nfs By Electrospinningmentioning
confidence: 99%
“…This method can minimize the loss of mechanical properties while ensuring the existence of the porous structure. Similarly, many multiple−chamber nanofibers, which are produced using multiple−fluid electrospinning and have been reviewed in some articles [ 168 , 169 , 170 , 171 , 172 ], can be similarly explored for achieving a general fine mechanical performance with the support from one of the chambers.…”
Section: Relationships Between Porous Structure and The Properties Of...mentioning
confidence: 99%